OPHTHALMOLOGICAL MANIFESTATIONS OF BEHÇET'S DISEASE IN ADOLESCENCE (CLINICAL CASE) (Neo Science Peer Reviewed Journal, 2025)
This paper presents a rare clinical case of ophthalmic manifestations of Behçet's disease in adolescence. The patient was diagnosed with recurrent anterior uveitis based on a comprehensive multidisciplinary evaluation. Treatment included pulse therapy with glucocorticoids, immunosuppressive and supportive therapy, leading to clinical improvement. This case highlights the importance of early diagnosis and multidisciplinary approach in the management of uveitis associated with Behçet's